Factors Associated with Employment for Graduates of Canadian Health Sciences Undergraduate University Programs - Yammine, Elena (Université d'Ottawa / University of Ottawa, 2016)
This project seeks to study the patterns of employment arising from an undergraduate education in health-related sciences. We employed descriptive and multivariate statistical methods to analyze two existing databases retrieved from Statistics Canada. The first source is the National Graduate Survey (NGS), and the second is the Labour Force Survey (LFS). We applied ordinary logistic regression to both the NGS and LFS to determine the statistically significant factors associated with successful employment in the health sector. Our results show that employability is associated with province, educational attainment, occupation, and industry. This study suggests that employed recent graduates employed in health-related industries were mainly employed in public sectors. Individuals who were employed in health-related industries were commonly young individuals. Individuals who graduated from health-related field of study also had one of the highest rates of working in their degree field. Most individuals working in a health science-related industry were part-time workers. A study of this nature can allow for the development of policies and standards to ensure students receive the appropriate training in health science-related university programs for future job prospects. Further research is needed to assess how much impact these factors have on the employability in health science-related industries for Canadian university graduates.